CCAFS Site Portfolio: Core Sites in the CCAFS Regions: East Africa, West Africa and South Asia - Förch, Wiebke; Kristjanson, Patricia M.; Thornton, Philip K.; Kiplimo, Joyce; Sijmons, Koert; Mutie, Ianetta; Cramer, Laura K.; Radeny, Maren A.O.; Moussa, Abdoulaye S.; Bhatta, Gopal Datt (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The CGIAR Research Program Climate Change, Agriculture, Food Security (CCAFS) is a 10-year research initiative launched by CGIAR and the Earth System Science Partnership (ESSP). CCAFS seeks to overcome the threats to agriculture and food security in a changing climate, exploring new ways of helping vulnerable rural communities adjust to global changes in climate. CCAFS brings together the world’s best researchers in agricultural science, development research, climate science, and Earth System science to identify and address the most important interactions, synergies and trade- offs between climate change, agriculture and food security. CCAFS also involves farmers, policy makers, donors, non-governmental organizations and other stakeholders to integrate their knowledge and needs into the tools and approaches that are being developed. The overall goal of CCAFS is to overcome the additional threats posed by a changing climate to achieving food security, enhancing livelihoods and improving environmental management. In 2010/2011, CCAFS initially focused on three regions: East Africa (EA), West Africa (WA) and South Asia (SA). Two additional target regions (Southeast Asia and Latin America) were added in late 2012. This report outlines the site selection process of current and future sites and provides a brief overview of the initially selected CCAFS sites.